A kinematic approach based on an equivalent track for a skid‐steering vehicle. Issue 1 (21st October 2015) - Galati, R.; Giannoccaro, N.I.; Messina, A.; Reina, G.
Abstract The skid‐steering principle is based on controlling the relative velocities of both the tracks as differential drive wheeled vehicles. However, control of tracked locomotion poses a more complex problem because variation of the relative velocity of the two tracks results often in slippage of the vehicle [1]. It is possible to define a kinematic approach able to describe and to improve the motion control and dead‐reckoning of a skid‐steering robot by considering the effects of the slippage but without introducing the complexity of dynamics computation. The equivalent track approach has been applied to a skid‐steering robot characterized by an high maximum payload (75 kg) and by a high power than makes it able to move in very difficult conditions (snow, iced terrains, mud) where the slippage effects become predominant. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)